Suria Luna Coffee House/ Asmaul Husna Zaini… [et.al.] - Zaini, Asmaul Husna; Abdullah, Hazerin; Junaidi, Nooraini; Ibrahim, Norhaiza; Mohd Mustafa, Siti Nurul Hidayah (2006)
Our business offered the customers with our various taste of coffee. Besides that, we also offer our customers with marvelous and delicious pastries that we get directly from our suppliers as we just focus on coffee drink. Our target market is the working groups, families, youth and foreigner with the project cost of RM 177,332.42. We also come up with projected first three years of sales and profit. For the year 2006, the projected sales are RM 473,277.42 and the profits are RM 10332.73. For the year 2007, the projected sales are RM 482,742.97 while the profits are RM 24793.28. For the year 2008, the projected sales are RM 498,225.26 and the profits are RM 39775.57.